Qualidade do sono e qualidade de vida no trabalho em trabalhadores industriais de turnos fixos - Pereira, Dante Luís (2014)
To analyze the existing correlation between Quality of Sleep (QS) and Life Quality at Work (LQW), on industrial workers with permanent or fixed work shifts. 134 production assistants were analyzed, distributed as Shift 1 (n=71) and Shift 2 (n=63). Two instruments were used: Pittsburgh Sleep Quality Index (PSQI), and Walton’s Questionnaire. In order to verify the correlation between QS and LQW the coefficient of Pearson was used. The analysis of each instrument was performed by the statistics of resume and analysis between “Shift 1” and “Shift 2”, using the Mann Wittney Test. As an add-on, the Data Mining technique, inside of a KDD (Knowledge Discovery in Database) process, using a WEKA GUI Chooser software, were also used. It was considered non-existent a correlation between QS and LQW. “Shift 2” showed superiority in comparison to “Shift 1” on LQW, with significant difference in the indicators of “social integration” and “constitutionalism”. “Shift 1” was superior in the indicators “work and life” and “use of capabilities”, both with a significant difference. In comparison to QS, “Shift 2” showed superiority over “Shift 1”, with significant difference in the components “quality of sleep”, “duration of sleep”, “efficiency of sleep” and “use of sleeping-aid medicines”, besides “global scoring of PSQI). A correlation between QS and LQW was not found, although, “Shift 2” is superior both in QS and LQW over “Shift 1”, that difference being significantly noticed only on QS.